The Effect of Human Resource Practices on Employee Loyalty: A Study of Banking Sector (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
The main purpose of this study is to evaluate the effect of human resource practices (HRM}  namely compensation, workplace, value & ethics, training, empowerment and leadership on  employee loyalty in banking sector organization of Mathura Region. This study was conducted  using self-administered questionnaire. Using a cross-sectional study, a valid questionnaire of  total l 00 employees of banking organization was collected using convenience sampling method.  The study has been conducted from the period of April 2018 to July 2018. Regression indicates  a significant and positive association of these practices with employee loyalty. The findings revealed  that these practices are highly influencing the employee loyalty and thereby enhancing the internal  efficiency.
Keywords: HRM Practices; Employee Loyalty